Using scRNA-seq to Identify Transcriptional Variation in the Malaria Parasite Ookinete Stage - Witmer, Kathrin; Dahalan, Farah Aida; Metcalf, Tom; Talman, Arthur M.; Howick, Virginia M.; Lawniczak, Mara K. N. (Frontiers in Cellular and Infection Microbiology, 2021)
The crossing of the mosquito midgut epithelium by the malaria parasite motile ookinete form represents the most extreme population bottleneck in the parasite life cycle and is a prime target for transmission blocking strategies. However, we have little understanding of the clonal variation that exists in a population of ookinetes in the vector, partially because the parasites are difficult to access and are found in low numbers. Within a vector, variation may result as a response to specific environmental cues or may exist independent of those cues as a potential bet-hedging strategy. Here we use single-cell RNA-seq to profile transcriptional variation in Plasmodium berghei ookinetes across different vector species, and between and within individual midguts. We then compare our results to low-input transcriptomes from individual Anopheles coluzzii midguts infected with the human malaria parasite Plasmodium falciparum. Although the vast majority of transcriptional changes in ookinetes are driven by development, we have identified candidate genes that may be responding to environmental cues or are clonally variant within a population. Our results illustrate the value of single-cell and low-input technologies in understanding clonal variation of parasite populations.